Urinary Neutrophil Gelatinase-Associated Lipocalin (uNGAL) and contrast-induced acute kidney injury after coronary angiogram (Swiss Medical Weekly, 2013)
QUESTIONS UNDER STUDY: Diagnosis of acute kidney injury (AKI) relies on measurement of serum creatinine (SCr). SCr is a late marker of impaired renal function. Urinary Neutrophil Gelatinase-Associated Lipocalin (uNGAL) has given encouraging results for an early and sensitive detection of AKI. This cohort study was conducted (1) to assess the value of uNGAL as early marker of contrast-induced AKI (CI-AKI) in unselected patients undergoing percutaneous coronary procedure (PCP) and (2) to investigate whether uNGAL levels correlate with the volume of contrast medium (CM) used during the procedure. METHODS: We enrolled 244 consecutive adult patients undergoing PCP done with the low-osmolar CM Iomeprolum (median volume of CM 122 [88–168] ml per procedure). uNGAL was measured at its peak with a standardised clinical laboratory platform (ARCHITECT uNGAL assay, Abbott). RESULTS: Overall, the post-PCP uNGAL levels were extremely low in our cohort with a median value of 7.7 [4.0–14.5] ng/ml (N ≤132 ng/ml). Twenty-five (10%) patients developed CI-AKI according to the classical diagnostic criteria (≥25% or ≥44.2 µmol/l increase in SCr) and 8 (3.3%) patients according to the AKIN criteria. Regardless of the definition considered, uNGAL levels did not significantly differ in patients with or without CI-AKI. Similarly, we found no significant correlation between the volume of CM used and the post-PCP uNGAL levels (r = –0.11). CONCLUSIONS: In a large cohort of unselected adult patients, uNGAL measured four to six hours after PCP was ineffective to predict the risk of CI-AKI and did not correlate with the volume of CM used during the procedure.